Concentration on Learning Program Development in Islamic Education - Dalmeri Mawardi; Supadi Supadi (Al-Hayat: Journal of Islamic Education, 2018)
An effort to educate learner in Islamic education as an order to the learner be able to change character and behavior. For Islamic education, learner hoped to be able to understand whole Islamic teachings and comprehend the aim of Islamic education entirely. Islamic subject Learning system has planned systematically and referred to learning components which have oriented to the new paradigm and the application of contextual teaching and learning approach; the class condition will be conducive and comfortable for the learner to be motivated to learn Islamic subject. In contextual teaching and learning approach be able to direct the process of Islamic teaching and learning for growing learner good behavior, character building, and moral values that will become human who has proper responsibility, emotional, intellectual, and human who has emotional intelligence in developing the learner potency in applying of Islamic educational making good relation between God with human being and doing whole Islamic teachings in Global Era. How the learner knows about Islamic teachings, but it discusses what has known and realized by learner after learning.? Learner hoped to be able to have a strong desire and a high commitment to understand and apply Islamic teachings.Suatu upaya mendidik peserta didik dalam pendidikan Islam agar siswa dapat mengubah karakter dan perilaku. Melalui pendidikan Islam, pelajar berharap dapat memahami seluruh ajaran Islam dan memahami sepenuhnya tujuan dari pendidikan Islam. Sistem pembelajaran mata pelajaran pendidikan Islam harus direncanakan secara sistematis dan harus mengacu pada komponen pembelajaran yang berorientasi pada paradigma baru dan penerapan pendekatan pembelajaran kontekstual, kondisi kelas akan kondusif dan mudah bagi peserta didik untuk termotivasi belajar Islam objek kajiannya. Tentunya pendekatan pembelajaran kontekstual dapat mengarahkan proses pembelajaran dan pembelajaran keislaman untuk menumbuhkan perilaku baik peserta didik, pembentukan karakter, dan nilai-nilai moral yang akan menjadi manusia yang memiliki tanggung jawab baik, emosional, intelektual, dan manusia yang memiliki kecerdasan emosional dalam mengembangkan potensi pelajar dalam menerapkan pendidikan Islam membuat hubungan yang baik antara Tuhan dengan manusia dan melakukan seluruh ajaran Islam di Era Global. Bagaimana pelajar tahu tentang ajaran Islam, tetapi membahas tentang apa yang telah diketahui dan disadari oleh pelajar setelah belajar? Setiap peserta didik dapat termotivasi serta memiliki keinginan yang kuat dan komitmen yang tinggi untuk mewujudkan dan menerapkan ajaran Islam.